Short chain acyl-CoA dehydrogenase deficiency and short-term high-fat diet perturb mitochondrial energy metabolism and transcriptional control of lipid-handling in liver. Issue 1 (December 2016) - Ghosh, Sujoy; Kruger, Claudia; Wicks, Shawna; Simon, Jacob; Kumar, K.; Johnson, William; Mynatt, Randall; Noland, Robert; Richards, Brenda
Abstract Background The liver is an important site of fat oxidation, which participates in the metabolic regulation of food intake. We showed previously that mice with genetically inactivatedAcads, encoding short-chain acyl-CoA dehydrogenase (SCAD), shift food consumption away from fat and toward carbohydrate when tested in a macronutrient choice paradigm. This phenotypic eating behavior suggests a link between fat oxidation and nutrient choice which may involve an energy sensing mechanism. To identify hepatic processes that could trigger energy-related signals, we have now performed transcriptional, metabolite and physiological analyses inAcads-/- mice following short-term (2 days) exposure to either high- or low-fat diet. Methods and Results Metabolite analysis revealed 25 acylcarnitine species that were altered by diet and/or genotype. Compared to wild-type mice, phosphorylated AMP-activated protein kinase was 40 % higher inAcads-/- mice after short-term high-fat diet, indicating a low ATP/AMP ratio. Metabolite analyses in isolated liver mitochondria fromAcads-/- mice during ADP-linked respiration on butyrate demonstrated a reduced oxygen consumption rate (OCR) compared to wild-type, an effect that was not observed with succinate or palmitoylcarnitine substrates. Liver transcriptomic responses inAcads-/- mice fed high- vs. lowfat diet revealed increased RXR/PPARA signaling, up-regulation of lipid handling pathways (including beta and omega oxidation), and increased mRNA expression of Nfe2l2 target genes. Conclusions Together, these results point to an oxidative shortage in this genetic model and support the hypothesis of a lower hepatic energy state associated with SCAD deficiency and high-fat diet.